JUNGIAN INDIVIDUATION IN RED DEAD REDEMPTION 2: ARCHETYPAL ANALYSIS OF ARTHUR MORGAN'S MORAL TRANSFORMATION - Al Ayyubi, Mohammad Taaba (ELite Journal : International Journal of Education, Language and Literature, 2026)
This study analyzes Red Dead Redemption 2 as a modern literary work by examining archetypes and symbolic themes in one of its most emotionally impactful scenes, commonly referred to by players as the "I'm Afraid" moment. Using Carl Jung's theories of archetypes and the process of individuation, the study examines two different versions of this crucial scenario: one with Sister Calderon and the other with Reverend Swanson, both of which demonstrate the main character's moral awakening. This paper uses data from a survey the researcher conducted previously to identify how players experienced the scene and what symbolic elements made it powerful. The study then explores how Red Dead Redemption 2, through its integration of narrative choice, moral consequence, and symbolic storytelling, expands the boundaries of modern literature. Unlike traditional forms, the game enables players to participate directly in the protagonist's emotional and philosophical development, demonstrating how interactivity can heighten literary engagement. By combining narrative depth with player agency, Red Dead Redemption 2 is positioned not merely as a game, but as a compelling example of contemporary literary experience that invites active moral and psychological participation.